PENGARUH KINERJA KEUANGAN TERHADAP FINANCIAL DISTRESS PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BEI - Miko Dwi Syahputra (2022)
This research is a quantitative study which aims to determine the effect of financial performance on financial distress. Measurement of financial performance is by using the ratio of liquidity, leverage, activity, and profitability. This study uses data from property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period, with a total sample of 45 companies. The sample selection in this study used a purposive sampling technique. The hypothesis testing tool used is logistic regression analysis using E-views 12.0 and Microsoft Excel 2016 software as data analysis tools. The results of this study are (1) liquidity has an effect on financial distress, (2) leverage has an effect on financial distress, (3) activity has no effect on financial distress, (4) profitability has an effect on financial distress.